TRENDS IN THE DEVELOPMENT OF HIGHER EDUCATION IN AUSTRALIA (Comparative Professional Pedagogy, 2022)
The study of foreign experience is necessary for innovative modernization of domestic higher education. Education in Australia guarantees successful studying, mastering of the latest technologies, promising development, and successful employment of graduates in the future. That is why interest in the development trends of higher education in this country is justified. The purpose of the article is to outline the main trends in the development of higher education in Australia. In the preparation of the article a number of theoretical methods were used. Among them are general scientific (analysis, synthesis, comparison, generalization, specification, which contributed to the identification of the main ideas for determining the key trends in the development of higher education in Australia) and specific scientific (cause and effect analysis, which helped to study the influence of international and state educational policies on the development of higher education in the country). The following main trends in the development of higher education in Australia have been identified: higher education sector is developing with state funding and on the basis of forward-looking government laws, improving conditions for the provision of educational services; the Australian system of higher education successfully cooperates with the European Higher Education Area, whose integration is based on thorough observance of national traditions and trends; there is close cooperation among enterprises and universities, support and development of scientific research; The National Workforce Strategy (2022–2027) defines a coordinated approach to solve the problem of personnel control (student employment and further professional development); lifelong learning is a link to educational success. Highlighting the main trends in the development of higher education in Australia will help to further determine the specifics of the professional training of specialists in English Philology at the country’s universities.
Keywords: Australian higher education; educational integration; National Workforce Strategy; continuing education; scientific research; cooperation between enterprises and universities